IMPLEMENTASI BUDAYA PELAYANAN PUBLIK PADA LAYANAN PASPOR BAGI WISATAWAN DI KANTOR IMIGRASI NGURAH RAI - Tania Audrey Sujanto; Made Artajaya; Putu Surya Laksana Rahjasa (Universitas Pendidikan Ganesha, 2026)
Quality public service is a key factor in improving satisfaction, including for tourists arranging their passports. This study analyses the implementation of public service culture in passport services for domestic tourists at the Ngurah Rai Class I Special Immigration Office. A descriptive qualitative method with a single-case design was applied, involving 15 purposively selected informants consisting of 4 officers and 11 tourist applicants. Data were gathered through observation, in-depth interviews, and documentation, then analysed through reduction, display, and conclusion drawing, and validated through triangulation. The findings reveal an uneven pattern: system-backed values of responsibility and equality have become institutionalised, whereas professionalism, friendliness, and transparency, which depend on personal interaction, remain inconsistent, especially at peak hours. The study frames passport processing as part of the tourist's pre-travel experience, so that the service culture of immigration offices helps shape the first impression of the journey.